Generation & Analysis of Harmonic for Various Combinations of Non-linear Load - Subhabrata Mukherjee; Kunal Chakraborty; Dipak Kumar Datta (Institute of Advanced Engineering and Science, 2014)
This paper refers to a comparative study of the harmonics generated by non-linear loads like compact fluorescent lamps (CFL). This work is carried out by measuring the frequency across the supply line by using CFL along with a resistive load. Here CF lamps are used as they are non-linear loads and generate frequencies of very high value. We have used three cfl lamps of different ratings such as 5, 14t and 20watt.